PENGEMBANGAN PENUNTUN PRATIKUM MATERI SISTEM PERNAPASAN UNTUK SISWA KELAS VIII SMP/MTs BERBASIS INKUIRI TERBIMBING - Mulyono; Rivo Yulse Viza; Leni Marlina (BIOCOLONY, 2021)
Based on research observations conducted by researchers at SMPN 50 Merangin, they still use the LKS book as a practical guide book at school. To overcome this problem, the research developed a practical guide for the respiratory system material based on guide inquiry. This study aims to produce an integrated science praticum guide based on guide in Quiry on the respiratory system material for class VIII students SMPN 50 so that is suitable to be used as a learning medium and also to produce an integrated science practicum guide based on Guide Inquiry on the design (planning), develop (development), and disseminate (Spread). In this study there were 5 (five) validators, 2 (two) people who will validate the practicum guide material the will be developed, namely 1 lecturer from the Biology study program and I science teacher at SMP N 50 Merangin. 1 (one) lecturer in the Indonesian language study program who will validate the language. 1 (one) STKIP YPM Bangko lecturer from mathematics study program who will validate the graph on display of the practical guide. The results of this study resulted in a product in the from of guided inquiry based practicum guide on respiratory system material. The feasibility of the practical guide on respiratory system material is proven from the results of the validator’s assessment that the average content feasibility obtained in 98,44% language is 87,5% presentation is 91,6% and graphic is 100%. With an average overall percentage of 94% (very valid).